Towards One Health clinical management of zoonoses: A parallel survey of Australian general medical practitioners and veterinarians. (31st December 2020) - Steele, Sandra G.; Booy, Robert; Manocha, Ramesh; Mor, Siobhan M.; Toribio, Jenny‐Ann L. M. L.
Abstract: General medical practitioners (GPs) and veterinarians have different but complementary knowledge and skills, with potential to enhance clinical management of zoonoses in human and animal patients through taking a One Health approach that promotes cross‐professional collaboration. Ability and willingness to engage within this framework is contingent on knowledge of endemic zoonoses and an understanding of the diversity of professional roles; however, previous research suggests that this is lacking. A unique parallel survey of Australian GPs and veterinarians was implemented to ascertain clinician experience, concern, confidence and current practices regarding zoonoses management as well as willingness to engage in cross‐professional collaboration where it is beneficial to overall health outcomes. Responses from 528 GPs and 605 veterinarians were analysed. Veterinarians in clinical practice were found to more frequently diagnose zoonoses; have greater concern about zoonoses; be more confident in diagnosing, managing and giving advice about the prevention of zoonoses; more likely to give advice about managing the risk of zoonoses; and more likely to initiate cross‐professional referral compared to GPs ( p  < .001 in all areas, adjusted for other factors). The findings of this study indicate a need for change in both clinical and continuing professional education, especially for GPs, in order to better equip them in the area of zoonoses management. Exploration of pathways to encourage and facilitate cross‐professional referral and collaboration will further improve clinical outcomes for both human and animal patients.